Thermal stability of nano-layered structure and hardness of TiAlN/Si3N4 nanoscale multilayered coating - Park, Jong-Keuk; Baik, Young-Joon (ELSEVIER, 2009)
Thermal stability of the TiAlN/Si3N4 nanoscale multilayered coating that was reported to show excellent hardness and toughness, has been investigated in terms of the nano-layered structure and hardness TiAlN/Si3N4 nanoscale multilayered coatings with various thickness of Si3N4 layer were prepared by alternating deposition of TiAlN and Si3N4. In contrast to other nanoscale multilayered coating system such as AlN/CrN in which the intensity of the low angle XRD peaks decreases with increasing annealing temperature by interdiffusion between adjacent layers, the low angle XRD peak intensity of the nanoscale multilayered TiAlN/Si3N4 coatings increased after heat-treatment in an N-2 atmosphere up to 800 degrees C. Such a thermal stability of the nano-layered structure is believed to be due to spinodal type phase separation of TiAlN and Si3N4, which increased the hardness value of the TiAlN/Si3N4 coating at high temperatures. (C) 2009 Elsevier B.V. All rights reserved.